Dampak Inovasi Produk, Strategi Harga, Dan Iklan Digital Terhadap Minat Beli Helm NHK di Kalangan Remaja Pengendara Motor - Dianti , Muthia Rahma; Zulstra, Jumadil Dwi; Rahim, Hamidah (CV. ITTC INDONESIA, 2025)
This study is motivated by a gap between NHK helmet product innovation and consumer expectations, a pricing strategy perceived as less competitive compared to rival brands, and digital advertising that has not effectively influenced consumer purchase intention. These issues highlight the need to evaluate the effectiveness of the marketing strategies implemented by the company. The purpose of this research is to analyze the influence of product innovation, pricing strategy, and digital advertising on consumer purchase intention toward NHK helmets. The study seeks to identify the most dominant factor affecting purchase decisions, providing a foundation for developing more effective marketing strategies. This research employs descriptive statistics and multiple linear regression analysis. Data were collected through questionnaires distributed to 100 respondents, specifically teenagers who use NHK helmets. The questionnaire was developed based on the indicators of the key variables: product innovation, pricing strategy, digital advertising, and purchase intention. This method was chosen to obtain primary data directly from respondents relevant to the research object. In addition, secondary data were sourced from company records, sales reports, and relevant literature to support the analysis. The results reveal that product innovation, pricing strategy, and digital advertising each have a significant effect on consumer purchase intention among teenage motorcycle users. Collectively, these variables contribute to shaping consumer interest in purchasing NHK helmets. The findings suggest that marketing strategies focusing on competitive pricing, improved product innovation, and targeted digital promotion through appropriate channels are more likely to enhance consumer interest and drive purchase behavior.